Automatic numerical-spatial association in synaesthesia: An fMRI investigation. (27th January 2017) - Arend, Isabel; Ashkenazi, Sarit; Yuen, Kenneth; Ofir, Shiran; Henik, Avishai
Abstract: A horizontal mental number line (MNL) is used to describe how quantities are represented across space. In humans, the neural correlates associated with such a representation are found in different areas of the posterior parietal cortex, especially, the intraparietal sulcus (IPS). In a phenomenon known as number-space synaesthesia, individuals visualise numbers in specific spatial locations. The experience of a MNL for number-space synaesthetes is explicit, idiosyncratic, and highly stable over time. It remains an open question whether the mechanisms underlying numerical-spatial association are shared by synaesthetes and nonsynaesthetes. We address the neural correlates of number-space association by examining the brain response in a number-space synaestheste (MkM) whose MNL differs dramatically in its ordinality and direction from that of a control group. MkM and 15 nonsynaesthetes compared the physical size of two numbers, while ignoring their numerical value, during an event-related functional magnetic resonance imaging session (fMRI). Two factors were analysed: the numerical distance effect (NDE; e.g., 2−4 small distance vs. 1−6 large distance), and the size congruity effect (e.g., 2−8 congruent vs. 2−8 incongruent). Only for MkM, the NDE elicited significant activity in the left and right IPS, supramarginal gyrus (bilateral), and in the left angular gyrus. These results strongly support the role of the parietal cortex in the automatic coding of space and quantity in number-space synaesthesia, even when numerical values are task-irrelevant. Highlights: Number-space synaesthetes visualise number in specific spatial locations. We addressed the neural correlates of such representation using fMRI. A synaesthete (MkM) and controls reported the physical size of numbers. Only for the synaesthete task-irrelevant numbers elicited parietal activity. Results implicate the parietal cortex in the automatic coding of space and numbers.